Spaces of Extraction in Europe: The Corporate–State–Mining Complex and Resistance in Greece and Romania - Konstantinos ‘Kostas’ Petrakos (Revue Internationale de Politique de Développement)
Despite the widespread attention paid to the spatial expansion of extractive frontiers around the globe, the multiple ways in which states and extractive transnational corporations interfere with and exercise authority over local populations in spaces of extraction remain underexplored. Drawing on insights from the literature on critical geography and on current debates over extractivism and neo-extractivism, this chapter explores the corporate strategies and techniques of power used in spaces of extraction, and discusses how states promote the forcible appropriation of land for mining operations. While most critical perspectives on extractivism have mainly focused on Latin America, Africa and Asia, where the expansion of extractive activities has intensified and become widespread, my focus is on the expansion of extractive activities in Europe, which has attracted renewed interest from extractive capital in the wake of the financial crisis. Two mining investments—by Eldorado Gold and Gabriel Resources, in Chalkidiki and Rosia Montană, respectively—have been reactivated in crisis-ridden Greece and Romania. In each country, a whole range of neo-liberal state strategies have paved the way for the expansion of the extractive frontier. Through an in-depth exploration of the two European cases examined here, this chapter builds on recent critical scholarship on new enclosures, extractivism, and the permanence of primitive accumulation in order to survey the inter-articulation of extractivist projects and neo-liberal policies in crisis-scapes. Attention given to social mobilisation at the extractive frontier highlights that social opposition arises due to some common agents of oppression. This social resistance leads to the formulation of a critique of development and highlights the importance of contesting neo-liberal policies at the international level.